2015
DOI: 10.1097/md.0000000000000545
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Evaluation Denture Adhesives Used by Patients With Xerostomia

Abstract: The purpose of study was to analyze the participants’ opinions concerning the effectiveness of 6 denture adhesives (DA).The study group included 60 participants. Criteria for selecting the patients were as follows: reduced retention and stabilization of maxillary complete dentures and xerostomia. These features were evaluated on basis of clinical examination and standard sialometry tests (u-SFR). Retention of maxillary dentures was scored by modified Kapur index before application of DA. All participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…One of the main goal of prosthetic treatment is to restore masticatory function in conventional denture wearers who suffer from decreased oral proprioception, alterations in chewing dynamics that occur with prosthetic devices and reduced denture stability and retention which is further compounded by physiologic bone resorption of the denturebearing ridge (17) . Again, the responses of the patients towards the tested adhesives were favouring their use as it improved their ability to chew and this is in accordance with multiple studies and surveys (9,10,17) . This may be attributed to the fact that improved retention and stability results in an increase in the force that can be applied during chewing, leading to fewer strokes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…One of the main goal of prosthetic treatment is to restore masticatory function in conventional denture wearers who suffer from decreased oral proprioception, alterations in chewing dynamics that occur with prosthetic devices and reduced denture stability and retention which is further compounded by physiologic bone resorption of the denturebearing ridge (17) . Again, the responses of the patients towards the tested adhesives were favouring their use as it improved their ability to chew and this is in accordance with multiple studies and surveys (9,10,17) . This may be attributed to the fact that improved retention and stability results in an increase in the force that can be applied during chewing, leading to fewer strokes.…”
Section: Discussionsupporting
confidence: 87%
“…It has been demonstrated that adhesives improve patient's satisfaction, bite force, masticatory efficacy, retention, and stability of dentures (6,8) , moreover, these advantages have been correlated to patients suffering from xerostomia (9) . Added to that, adhesives reduce three-dimensional and rotational denture movements and chewing times in old and new dentures therefore improve chewing function (10) .…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations were made by Bogucki et al, who identified a correlation between xerostomia, medication taken by patients, age, gender and past diseases. 35 The total OHIP-14 score in the examined subjects aged 65 and over was 8.01 ±13.59 and it did reveal a significant difference related to the gender. Comparing the figure in the same age group of different populations, we noticed a slightly higher value (8.88) in Spain 36 , 2.8-fold higher (22.4) in Iran 37 and 2.7-fold lower (2.9) in the United Kingdom.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, a shortening of masticating cycle time and increases in occlusal force and masticating rate have been observed with DA application [14][15][16] . It has also been found that DA influence the retentive force of dentures worn by patients with xerostomia 17,18) . Moreover, DA use in combination with diet therapy can lead to improvements in eating behavior by complete denture wearers 19) .…”
Section: Introductionmentioning
confidence: 99%